Removal of Remazol Brilliant Blue R from Aqueous Solution by Adsorption Using Pineapple Leaf Powder and Lime Peel Powder - Normaizatul Akmar, Rahmat; Aili Aqilah, Ali; Salmiati; Nafsiah, Hussain; Mimi Suliza, Muhamad; Risky Ayu, Kristanti; Hadibarata, Tony (Springer Netherlands, 2016)
Wide use of dyes in production of fabric becomes the most problematic and generates high amount of liquid effluent pollutants to the surface water. The potential of waste materials, pineapple (Ananas comosus) leaf powder and lime (Citrus aurantifolia) peel powder, to remove Remazol Brilliant Blue R (RBBR) from aqueous solution through adsorption process was investigated. Batch experiments were conducted at initial dye concentration of 500 mg/L. Data analysis showed a removal percentage more than 90 %. The Langmuir, Freundlich, and Temkin isotherm models were also investigated to study the mechanism of dye molecules onto adsorption process. The optimum equilibrium was obtained by the Langmuir isotherm (R 2 = 0.9945) for pineapple leaves and (R 2 = 0.9994) for lime peel. The maximum monolayer adsorption capacity adsorbents onto RBBR (9.58 mg/g) were achieved. The pseudo-second-order kinetic indicates that the rate constant was 1.00. The specific area of both adsorbents was identified as homogenous structure and was characterized by field emission scanning electron microscopy (FESEM) analysis. The surface functional groups responsible for dye uptake by adsorbents indicate that both adsorbents were defined as carboxyl group which consists of carbonyl and hydroxyl groups and were analyzed by Fourier transform infrared spectrometry (FTIR) analysis. The overall study indicates that adsorbents prepared from pineapple leaves and lime peels are alternative low-cost product in dye removal from aqueous solution.